Pediatric-acquired Idiopathic Blepharoptosis with the Eyelids Being Habitually Opened Using the Frontalis Muscle - Naohiro Ishii, MD, PhD; Takanori Ko, MD; Tomoki Kiuchi, MD; Makoto Shimabukuro, MD; Kyoichi Matsuzaki, MD, PhD; Kazuo Kishi, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. Pediatric-acquired idiopathic blepharoptosis is rare, and no studies on surgery for the disease have been reported. We present a case of the disease with an atypical postoperative course. The patient initially underwent levator aponeurosis advancement. However, she cannot sufficiently open the affected eyelid without conscious effort and has developed a habit of opening the eyelids using the frontalis muscle. She underwent secondary frontalis suspension with the fascia latae, and then she was able to open her eyelids well all the time. When the disease duration in pediatric-acquired blepharoptosis is long, the habit of opening the eyelids using the frontalis muscle may be difficult to break. In such cases, we believe that frontalis suspension is the best operation.